The study of anaplasma and ehrlichia genetic variability in parasitic systems in the South-Western Siberia and Ural - V. A. Rar; N. N. Livanova; V. V. Panov; V. B. Astanin; S. G. Livanov; O. V. Morozova (Бюллетень сибирской медицины, 2006)
Ehrlichia muris and Anaplasma phagocytophilum DNA were detected using nested PCR among Ixodes persulcatus collected in Novosibirsk, Sverdlovsk and Chelyabinsk regions and in blood samples of small mammals from Novosibirsk and Sverdlovsk re- gions. Two genetic variants of A. phagocytophilum were revealed in blood samples and ticks from Novosibirsk region.